TRANSSPHENOIDAL SURGERY OF NASAL LIQUORRHEA AS A COMPLICATION AFTER TREATMENT OF PROLACTINOMAS WITH DRUGS - A. V. Polezhaev; V. Yu. Cherebillo; D. V. Svistov; U. A. Tsoy; D. V. Voitsekhovsky (Вестник хирургии имени И.И. Грекова)
The objective of the research is to optimize the method of transnasal endoscopic plasty of liquor fistulas in patients with prolactinomas, who got nasal liquorrhea against the background of treatment with dopamine agonists.Material and methods. Transnasal endoscopic approach was performed in 7 cases with prolactinomas. There were 9 operations including 2 interventions caused by liquorrhea relapse. Plasty with Tachocomb and biological adhesives were used in 2 cases. The other 7 cases demanded additional use of an adipose tissue fragment.Results. Complete arrest of liquorrhea was achieved in 5 cases. It resumed in 2 patients who had undergone plasty with Tachcomb and biological adhesives. They needed into the reoperations with use of autoadipose tissue.Conclusion. Using of CTcisternography is necessary for revealing exact localization of liquor fistula. It is expedient to apply Tachocomb and a fragment of autoadipose tissue fixed with biological adhesives. Discontinuation of treatment with Cabergoline for a month is recommended after the operation.